Optic pathway gliomas in adolescence—time to challenge treatment choices? - Lee Chong, Amy (Oxford University Press, 2013)
BACKGROUND: Optimal management of optic pathway/hypothalamic glioma (OPHG) remains an ongoing challenge. Little is known about the natural history, management strategies, and outcomes in adolescents. Carboplatin-based chemotherapy is a useful modality in younger children, delaying radiation to their immature brains. National trials have focused on younger children and excluded adolescents from studies evaluating the role of chemotherapy. METHODS: This retrospective study describes clinical characteristics, treatment regimens, and outcomes in adolescents (aged ≥10 years) with OPHG (diagnosis during 1990–2006). Progression-free survival was compared with that in a cohort of younger children (aged <10 years). RESULTS: Thirty-three adolescents (19 females, 6 with neurofibromatosis type 1) with OPHG were identified within 2 Canadian pediatric oncology institutions. The majority presented with visual symptoms (82%). More than 55% (18 of 33) involved the posterior tract and/or hypothalamus (modified Dodge classification 3/4). Seventeen were initially observed; 8 remained progression free. Of the 25 of 33 adolescents who required active treatment, 9 (36%) needed second-line therapy. The progression-free survival for any first active treatment at age <10 years (52 of 102) or ≥10 years (25 of 33) was similar (46.9 vs 46.8 months; P = .60). In those who received chemotherapy as first-line treatment or after prior nonchemotherapy treatment failure, the progression-free survival trend was superior (62.9 vs 38.9 months) in those aged ≥10 years although not statistically significant (P = .16). CONCLUSIONS: Chemotherapy is a valuable treatment modality for the achievement of disease control even in adolescents; their progression-free survival compares favorably with that in younger children. We propose that chemotherapy be considered as a first-line modality in adolescents, avoiding potential radiation-associated morbidities.